Living Happily in the Era of COVID-19: Philosophical and Positive Psychology Intervention in Secondary Education - Michopoulou, Eleni (Conatus - Journal of Philosophy, 2022)
In the coronavirus pandemic crisis, the mental well-being of adolescents was significantly burdened and, in this context, an innovative school intervention program was applied and its effect was investigated. The program involved a structured 11-weeks-long psycho-educational intervention on a sample of 11 Greek high school students (aged 16-17 years), combining principles of Epicurean and Stoic Philosophy with Positive Psychology techniques, aiming at promoting their mental well-being and the effective management of the psychological effects of the pandemic crisis. A qualitative methodology was used for data collection, including triangulation and data enrichment, self-referential demographic questionnaires, focus group and group interviews, semi-structured individual oral interviews and written descriptions and narratives. Before the intervention, the students’ needs and expectations were investigated through written narratives and, after the intervention, semi-structured individual oral interviews and group interviews recorded their personal experiences and evaluative judgments. The application of positive techniques of meaning in life, optimism, gratitude and the development of positive relationships, combined with a cognitive reconstruction based on the principles of Epicureanism and Stoicism, had beneficial effects on the participating students, including emotional state improvement, mental well-being enhancement, and improved aspects of quality of life, such as subjective health, cognitive and school performance, family and interpersonal relationships. The highlight of the study was the emergence of the supporting role of Philosophy in the effectiveness of the applied techniques of Positive Psychology in the management of the psychological and social impact of the COVID-19 pandemic.